Celecoxib Blocks Vasculogenic Mimicry via an Off-Target Effect to Radiosensitize Lung Cancer Cells: An Experimental Study - Niu, Kai; Chen, Xie-Wan; Qin, Yu; Zhang, Lu-Ping; Liao, Rong-Xia; Sun, Jian-Guo (Frontiers in Oncology, 2021)
The resistance to radiotherapy in lung cancer can be attributed to vasculogenic mimicry (VM) to some extent. Celecoxib (CXB), a selective inhibitor of cyclooxygenase-2 (COX-2), is reported as a radiosensitizer in non-small cell lung cancer (NSCLC). However, whether CXB can regulate VM formation via an off-target effect to radiosensitize NSCLC remains unclear. This study aimed to elucidate the mechanism underlying the radiosensitizing effect of CXB on NSCLC, i.e., whether CXB can inhibit VM formation via binding to newly identified targets other than COX-2. CXB radiosensitivity assay was performed in BALB/c mice bearing H460 xenografts and C57 mice bearing Lewis lung cancer (LLC) xenografts, which were divided into the control, CXB, irradiation (IR) treatment, and IR plus CXB groups. VM formation was observed using 3D Matrigel, periodic acid solution (PAS) staining, and immunofluorescence staining. The potential off-targets of CXB were screened using Protein Data Bank (PDB) database, MGLTools 1.5.6, and AutoDock Vina 1.1.2 and confirmed by Western blotting, enzyme activity assay, and RNA interference in vitro experiments and by immunohistochemistry in vivo experiments. CXB treatment almost eliminated the enhancement of VM formation by IR in vitro and in vivo, partially due to COX-2 inhibition. Four potential off-targets were predicted by molecular docking. Among them, aminopeptidase N (APN) and integrin alpha-V (ITAV) were remarkably inhibited in protein expression and enzyme activity in vitro or in vivo, consistent with the remarkable reduction of VM formation in H460 xenografts in BALB/c mice. In conclusion, CXB dramatically blocked VM through inhibiting newly identified off-targets APN and ITAV, other than COX-2, then radiosensitizing NSCLC.